2007
DOI: 10.1097/cmr.0b013e3280dec6ac
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 (COX-2): first immunohistochemical marker distinguishing early cutaneous melanomas from benign melanocytic skin tumours

Abstract: We have reported recently that changes in expression level of COX-2 are correlated with development and progression of human melanoma. In this study, we investigated whether the COX-2 expression level might be a useful immunohistochemical marker for distinguishing cutaneous melanomas from benign melanocytic lesions. Up to now, immunohistochemical markers have not ensured satisfactory sensitivity and specificity of differential pathologic diagnosis of melanoma. The expression of COX-2 was determined immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…In this work, and in our earlier studies of COX-2 in melanocytic cutaneous lesions and in adjacent skin [31,32], we have consistently observed in a large number of samples of normal human skin positive staining of keratinocytes of the granular and spinous layers. Our present study demonstrated that papillomas, verrucas and normal skin express COX-2 at comparable levels.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this work, and in our earlier studies of COX-2 in melanocytic cutaneous lesions and in adjacent skin [31,32], we have consistently observed in a large number of samples of normal human skin positive staining of keratinocytes of the granular and spinous layers. Our present study demonstrated that papillomas, verrucas and normal skin express COX-2 at comparable levels.…”
Section: Discussionsupporting
confidence: 81%
“…Our studies have demonstrated that the development and progression of human cutaneous melanoma are accompanied by a clear increase of COX-2 expression in melanocytes [31,32]. It should be noted that earlier data on COX-2 expression in 382 382 382 382 382 [33].…”
Section: Introduction Introduction Introduction Introduction Introducsupporting
confidence: 50%
“…Recent clinical trials of the specific COX-2 inhibitor celecoxib suggest that COX-2 inhibition may increase the clinical efficacy of temozolomide for melanoma treatment (Gogas et al, 2006). Furthermore, as COX-2 is more highly expressed in cutaneous melanoma and metastatic melanoma compared with benign naevi (Chwirot and Kuzbicki, 2007), defining upstream regulators could be valuable for drug development. Pertinent to cancer pathogenesis and metastasis, c-myc and VEGF are additional transcriptional targets of NFAT (Buchholz and Ellenrieder, 2007), further emphasising the relevance of NFAT signalling for melanoma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accumulating evidence suggests that increased NFAT transcriptional activity contributes to both the development and progression of cancer (Buchholz and Ellenrieder, 2007), and identifies NFAT signalling as a potential target for cancer therapy. In the context of melanoma, increased expression of the NFAT target gene cyclooxygenase-2 (COX-2), an inducible enzyme involved in the conversion of arachidonic acid to prostaglandins, correlates with poor prognosis (Kuzbicki et al, 2006;Chwirot and Kuzbicki, 2007), suggesting that NFAT signalling may be important in melanoma. However, upstream activators of COX-2 in melanoma and a role for oncogene-driven NFAT activation remain undefined.…”
mentioning
confidence: 99%
“…It has been suggested that GPC3 may be a useful early stage biomarker for patients with the early stages of the disease (0 -II) (Nakatsura et al, 2004;Ikuta et al, 2005). Moreover, cyclooxygenase-2 (COX-2) (Chwirot and Kuźbicki, 2007), serum amyloid A (SAA) (Mian et al, 2005;Findeisen et al, 2009) and DNA methylation profiling (Conway et al, 2011) can be used to distinguish between early melanomas and benign nevi.…”
Section: Biomarkers For Early Melanoma Diagnosismentioning
confidence: 99%